2004
DOI: 10.22358/jafs/70284/2004
|View full text |Cite
|
Sign up to set email alerts
|

Linseed-based diets for sheep. 2. Performance and chemical composition of meat and liver

Abstract: The effects of dietary linseed cultivars, traditional (Opal, Omega) or the new Linola cultivar with an increased content of linoleic acid, on the performance and chemical composition of lamb meat and liver were investigated. The animals were fed meadow hay and concentrate. The control group received no linseed in concentrate, whereas the experimental groups received 10% crushed linseed of different cultivars. There was no significant effect of linseed, irrespective of cultivar, on daily weight gains of the lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
2
3
0
2
Order By: Relevance
“…The major synthesis pathway of the CLA isomer, rumenic acid, in the tissues of ruminants is primarily from the biohydrogenation of ALA into vaccenic acid (C18:1n-7) catalyzed by reductase enzymes [76,77]. The variation patterns and ranges in liver fatty acid profiles in the present study were similar to previously reported findings [78][79][80][81][82][83]. The liver has also been reported to have a high nutrient content of essential amino acids, fatty acids, iron, zinc, magnesium, selenium, calcium, vitamins B1, B6, B12, and folic acid [84,85] and may explain why duck liver attracts a price premium and is consumed in France [86].…”
Section: Discussionsupporting
confidence: 90%
“…The major synthesis pathway of the CLA isomer, rumenic acid, in the tissues of ruminants is primarily from the biohydrogenation of ALA into vaccenic acid (C18:1n-7) catalyzed by reductase enzymes [76,77]. The variation patterns and ranges in liver fatty acid profiles in the present study were similar to previously reported findings [78][79][80][81][82][83]. The liver has also been reported to have a high nutrient content of essential amino acids, fatty acids, iron, zinc, magnesium, selenium, calcium, vitamins B1, B6, B12, and folic acid [84,85] and may explain why duck liver attracts a price premium and is consumed in France [86].…”
Section: Discussionsupporting
confidence: 90%
“…These results agree with those reported by (37) when lambs fed diet supplemented with linseed oil and mineral bioplex. Similar findings were observed by many other reports (32,38,39). The effect of ground flaxseed GF supplementation on rib eye area and fat thickness which are presented in table 3.…”
Section: Resultssupporting
confidence: 89%
“…These results might be caused by increases in the concentration of free amino acids, glutamic acid, methionine, and α-AAA, and peptides, anserine and carnosine, and their complex reactions. Some studies have shown that carcass traits under way to increase the concentration of unsaturated fatty acids (UFA) using vegetable or fish oil supplements in feeds and to reduce the level of cholesterol in animal products through appropriate nutrition: (30), eggs (31) and meat (32). Several feed strategies have been tested to increase the n-3 UFA content of lamb meat such as fish oil used in the past or more recently vegetable sources like linseed.…”
Section: Introductionmentioning
confidence: 99%
“…Borowiec i wsp. [5] nie potwierdzili statystycznie istotnego wpływu skarmiania mieszanek z 10-procentowym udziałem nasion lnu różnych odmian na przyrosty masy ciała jagniąt, wykorzystanie paszy, wydajność rzeźną i skład chemiczny mięsa. Jakość mięsa W badaniach własnych nie zaobserwowano wpływu uzupełnienia mieszanki treściwej nasionami lnu w ilości 5 % na podstawowy skład chemiczny mięsa (tab.…”
Section: Cechy Tuczne I Rzeźneunclassified
“…W badaniach przeprowadzonych przez Borowca i wsp. [5] oraz Micka i wsp. [11], dodatek nasion lnu spowodował wzrost sumy nienasyconych kwasów tłuszczowych (UFA) mięsa jagniąt w grupach doświadczalnych.…”
Section: Cechy Tuczne I Rzeźneunclassified